Speech-Induced Suppression for Delayed Auditory Feedback in Adults Who Do and Do Not Stutter - Toyomura, Akira; Miyashiro, Daiki; Kuriki, Shinya; Sowman, Paul F. (Frontiers in Human Neuroscience, 2020)
Speech-induced suppression is the normal, relative amplitude reduction of the auditory evoked potential for self-, compared to externally-generated, auditory stimulation. It remains controversial as to whether adults who stutter exhibit expected auditory modulation during speech; some studies have reported a significant difference between stuttering and fluent groups in speech-induced suppression during speech movement planning, while others have not. We compared the auditory evoked potentials (N1 component) for auditory feedback arising from one’s own voice (Speaking condition) with passive listening to a recording of one’s own voice (Listening condition) in 24 normally-fluent speakers and 16 adults who stutter under various delayed auditory feedback (DAF) time conditions (100 ms, 200 ms, 500 ms, and 1000 ms). We presented the participant's own voice with a delay, immediately after presenting it without a delay. Our working hypothesis was that the shorter the delay time, the more likely the delayed sound is perceived as self-generated. Therefore, shorter delay time conditions are proposed to result in relatively enhanced suppression of the auditory system. The results showed that in fluent speakers, the shorter the delay time, the more the auditory evoked potential in the Speaking condition tended to be suppressed. In the Listening condition there was a larger evoked potential with shorter delay times. As a result, speech-induced suppression was only significant at the short delay time conditions of 100 and 200 ms. Adults who stutter did not show the opposing changes in the Speaking and Listening conditions seen in the fluent group. Although the evoked potential in the Listening condition tended to decrease as the delay time increased, that in the Speaking condition did not show a distinct trend, and there was a significant suppression only at 200 ms delay. For the 200 ms delay condition, speakers with more severe stuttering showed significantly greater speech-induced suppression than those with less severe stuttering. This preliminary study suggests our methods for investigating evoked potentials by presenting own voice with a delay may provide a clue as to the nature of auditory modulation in stuttering.